2017
DOI: 10.4236/ijmnta.2017.61003
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Control of Chaotic Forced Duffing and Van der Pol Oscillators

Abstract: This paper discusses a novel technique and implementation to perform nonlinear control for two different forced model state oscillators and actuators. The paper starts by discussing the Duffing oscillator which features a second order non-linear differential equation describing complex motion whereas the second model is the Van der Pol oscillator with non-linear damping. A first order actuator is added to both models to expand on the chaotic behavior of the oscillators. In order to control the system without c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Lyapunov control has proven successful in managing complex nonlinear oscillators to a certain extent of oscillator frequency ω = 2.5 Hz [7]. In order to improve the system stability at a higher ω, deep learning was introduced in [4].…”
Section: Design Of the Lyapunov Controllermentioning
confidence: 99%
See 2 more Smart Citations
“…Lyapunov control has proven successful in managing complex nonlinear oscillators to a certain extent of oscillator frequency ω = 2.5 Hz [7]. In order to improve the system stability at a higher ω, deep learning was introduced in [4].…”
Section: Design Of the Lyapunov Controllermentioning
confidence: 99%
“…The research completed in [7] revealed that the controller parameters had substantial impact on the desired system outcome and error; therefore, the research in [4] successfully presented a deep learning approach that would allow 1 of the controller parameters to change while the system is operational thus tackling sudden changes in stability. One of the disadvantages found through the survey in [10] is that the system learning/relearning process robustness is significantly reduced if more parameters require updates simultaneously.…”
Section: Deep Learning Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Near a bifurcation point, the system’s state becomes slower. In other words, the transient time increases near a bifurcation point [ 46 , 47 ]. In order to use Kolmogorov–Sinai entropy to anticipate a bifurcation point, we calculated it without removing the transient time of the trajectory.…”
Section: Entropy Analysismentioning
confidence: 99%
“…The purpose of these transformations is to simplify the equations so as to be able to use numerical methods to solve them [3,4]. A great number of physical systems are modelled by second-order ODEs, for example, the Duffing or Van der Pol equations [3,5,6,7,8,9]. These equations, after their transformation into a system of equations, are analysed on the phase plane.…”
Section: Introductionmentioning
confidence: 99%